Sensitization to Malassezia in children with atopic dermatitis combined with food allergy. Issue 3 (3rd April 2013) - Kekki, O‐M.; Scheynius, A.; Poikonen, S.; Koskinen, A.; Kautiainen, H.; Turjanmaa, K.
Abstract: Background: The yeast Malassezia belongs to our normal cutaneous flora, but is capable of sensitizing individuals with atopic dermatitis (AD). Our objective was to investigate the prevalence of sensitization to Malassezia with a 10‐yr follow‐up among children suffering from AD combined with food allergy (FA) in relation to the extent of AD in infancy. Methods: One hundred and eighty seven infants diagnosed with AD and milk/wheat allergy before 1 yr of age were included in the study. The area of AD was estimated from patient records of the first visit and measured with SCORAD at the 10‐yr follow‐up. Specific IgE against Malassezia was determined with ImmunoCAP™ at 11 yr of age. Results: In infancy, 24 children (13%) were allergic to milk, 71 (38%) to wheat, and 92 (49%) to both milk and wheat, and 94 (50%) children had mild, 57 (30%) moderate and 36 (19%) severe AD. At the 10‐yr follow‐up visit, 19 (10%) of the children had ongoing milk and/or wheat allergy; 147 children (79%) had mild AD and 30 (16%) had SCORAD index of 0. Specific IgE against Malassezia mix was positive (≥0.35 kU/l) in 27% and specific IgE against M. sympodialis in 20% of the 187 children. The area of AD in infancy was associated with a greater risk of having allergen‐specific IgE to Malassezia at the 10‐yr follow‐up. The risk ratio for FA was 3.11 (95% CI: 2.05–4.72; p < 0.001) if specific IgE to Malassezia was positive. Conclusions: Infants with severe AD and FA seem to have a greater risk of becoming sensitized to Malassezia during a 10‐yr follow‐up.